Text Of Women's Theater in Kurdish Theatre - Hawnaz Hussein Ismail Ahmad; Kaify Ahmad Abdulqader (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The situations in which women have lived in ancient centuries and past civilizations are not hidden from anyone, which is full of suffering and misery. Women have always faced many problems and difficulties; women's theater has an impact on the creation and production of human thoughts, and After the 1970s, a group of women played a significant role in writing literary articles, while initially women had been deprived of all rights and duties. Women's participation in all literary subjects and other aspects has been generally low. If we look at the difference between the writing of women's and men's theatrical texts we find that most of the theatrical texts, especially in Kurdistan, are generally male theater. From the very beginning of theater, men have been the leaders in writing, directing, the way of managing it. Therefore, they have paid less attention to women's problems, sufferings, difficulties and opinions, which express women and their thoughts. The research is entitled "Women's Theater Texts in Kurdish Theater" and consists of an introduction, two parts and a conclusion, each part consisting of several topics.